Strange Wines. Dealcoholised Wine at the Crossroads of Science, Identity, and the Politics of Drinking - Puca, Davide (E|C, 2025)
This paper examines the rise of dealcoholised wines through the lens of contemporary health discourse, identity politics, and evolving consumption practices, with a focus on the Italian context. It explores how wine is increasingly framed not only as a cultural and gastronomic emblem but also as a public health concern, sparking tensions between tradition and regulation, particularly following the Irish labelling initiative. Through a sociosemiotic approach, the study analyses exemplary media texts, public statements, and branding strategies to uncover the values and narratives at play. It argues that dealcoholisation reshapes both the semiotic and market identity of wine, revealing the complex entanglement of science, politics, and consumer culture in today’s alcohol debate.